AB0221 Impact of small to medium dose of prednisolone on bone mineral density among early rheumatoid arthritis patients. (15th June 2017) - Lam, HM; Wan, MC; Tam, LS; ,
Abstract : Background: Recent randomized trials in rheumatoid arthritis (RA) using low to medium dose of corticosteroid showed that bone mineral density (BMD) loss over 2 years was not significantly different from that with placebo. Another study in early RA and undifferentiated arthritis even showed a positive correlation between cumulative glucocorticoid (GC) dose with an increase in BMD at the ultradistal forearm. Whether the use of prednisolone (pred) can prevent bone loss in early RA patients remained controversial. Objectives: The aim of this study was to investigate the impact of small dose pred (≤10mg/day) on BMD in early RA patients. Methods: Data from 107 patients ((age: 53.3±11.92 years; females: 79 [73.8%], median disease duration at entry: 7-month (IQR, 4–12)) from the Hong Kong early arthritis registry (Clinical Rheumatology Systematic Treat to Target in Asia Leadership [CRYSTAL] project)were analyzed. In this register, clinical and treatment information were recorded systematically, including cumulative GC dose. Hip, spine and forearm BMDs were measured by duel-energy X-ray absorptiometry (DXA) at baseline and month 12. Patients were categorized into three groups according to pred use (never/<3/≥3 months) during the first year of follow-up. Patients who ever took>10mg/day of pred were excluded. The change in BMD was compared between groups and between the two time points. Results: The baseline characteristics of patients were shown in Table 1 . Patients who required ≥3 months of pred treatment are older, with a shorter disease duration and a higher disease activity. Significant differences in the percentage change of BMD in forearm was found among the groups (Pred never/Pred<3 months/Pred≥3 months: -2.99±4.21/-1.05±3.10/-0.65±3.45, p =0.045). Post-hoc analysis revealed that the percentage reduction of forearm BMD was significantly less in the Pred ≥3 months group compared to the Pred never group ( p =0.043). After adjusting for age, gender, disease duration and baseline DAS-CRP, the changes in forearm BMD was still significantly different among the three groups ( p =0.015). No significant differences in the changes of hip and spine BMD were observed. Significant changes in forearm BMD were observed between baseline and month 12 only in the Pred never group (0.54±0.08/0.53±0.0 p <0.001, graph1). Conclusions: Small to medium dose of prednisolone might protect bone loss in forearm among early RA patients. These results need to be further validated. References: Safety of low- to medium-dose glucocorticoid treatment in rheumatoid arthritis: myths and reality over the years. Ann N Y Acad Sci 2014. Disclosure of Interest: None declared